UNPACKING THE LANDSCAPE OF DIGITAL AND CORPORATE ENTREPRENEURSHIP: A SYSTEMATIC LITERATURE REVIEW OF KEY CHARACTERISTICS, DIMENSIONS, AND STRATEGIC OUTCOME - Ristiaji Ari Wibowo; Sri Setyo Iriani; Raya Sulistyowati; M. Azizul Khakim; Novie Noordiana Rachma Yulia; Roos Nana Sucihati (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The advancement of digital technology has revolutionized the global entrepreneurial landscape, giving rise to two primary approaches digital entrepreneurship and corporate entrepreneurship. This study is motivated by the need to understand the differences, similarities, and synergies between these two approaches in addressing increasingly complex and dynamic business challenges. The main objective of this study is to identify the key characteristics, dimensions, and strategic outcomes of both entrepreneurial models. Employing a Systematic Literature Review (SLR) method guided by the PRISMA framework, the study examines 18 relevant scholarly articles published between 2018 and 2024. Data were obtained through a systematic process of identification, selection, and evaluation of literature from the Scopus database. The findings indicate that digital entrepreneurship emphasizes flexibility, external exploration, and the utilization of technology as a value creation tool, whereas corporate entrepreneurship focuses more on the exploitation of internal resources, structured innovation, and operational efficiency. This study reveals that, despite their differing approaches, the strategic integration of digital and corporate entrepreneurship can foster the development of ambidextrous organizations those capable of balancing exploration and exploitation simultaneously. The conclusion underscores the importance of building entrepreneurial agility, integrating digital technologies, and strengthening entrepreneurship education as critical foundations for achieving sustainable competitive advantage in the digital era. Keywords: Corporate Entrepreneurship ; Digital Entrepreneurship; Digital Transformation; Strategic Innovation; Systematic Literature Review